A Facile Synthesis of Novel Cyclic Esters of γ‐Keto Acid Derivatives by Heck Coupling Reaction. (25th April 2014) - Shashikumar, Nellisara D.; Krishnamurthy, G.; Bhojyanaik, Halehatti S.
<x xml:space="preserve">Abstract</x> γ‐Keto acids and esters are highly useful compounds in organic synthesis, because a number of five‐membered carbocycles and various other heterocycles can be readily obtained from them. A number of γ‐keto acids derivatives have been synthesized with high yield by Heck coupling reaction with different alkenes using Pd(OAc)2 as catalyst in dioxane solvent. The obtained products were characterized by elemental analysis, IR, proton NMR, and mass spectral studies.